Development of a versatile analytical protocol for the comprehensive determination of the elemental composition of smartphone compartments on the example of printed circuit boards. Issue 31 (31st July 2018) - Bookhagen, B.; Obermaier, W.; Opper, C.; Koeberl, C.; Hofmann, T.; Prohaska, T.; Irrgeher, J.
Abstract : A comprehensive method for the determination of metals in electronic devices was developed and tested on smartphones. Abstract : A versatile approach to determining the elemental content of more than 50 elements in different components of electronic devices on the example of smartphones was developed. The analytical protocol is based on accurate disassembly of smartphones, a single processing microwave-assisted acid digestion followed by ICP-OES and ICP-MS measurements. Method optimization and validation were performed using the certified reference material ERM®-EZ505 electronic scrap. Combined uncertainties revealed measurement uncertainty and sample heterogeneity as main contributors. The contents of up to 57 elements could be quantified in the certified reference material ERM®-EZ505 electronic scrap. The results of the certified elements Au, Be, Cu, In, Ni, Pd, and Pt overlapped within their uncertainties with the certified range and revealed recoveries of 100% ± 16%. Only Ag shows incomplete recoveries (75% ± 35%). The validated method was applied to all metal-containing components of selected smartphones, excluding batteries. The contents of up to 57 elements could be quantified and are presented exemplarily for printed circuit boards, which represent the most complex components in the investigated smartphones and thus limit the capability of the method. The ten most abundant elements in decreasing order are Cu, Fe, Si, Ni, Sn, Zn, Ba, Al, Cr, Ti, which comprise approx. 80% of the weight of the printed circuit boards. The method allows for the determination of metal content in various parts of modern smartphones, providing the basis for the estimation and prediction of future metal usage and thus the comprehensive investigation of recycling and circular economy aspects.